Contributions Created on Spaces of Collective Virtual Intelligence and Their Projection in Video Game Sound Design: The fandom community of the video game No Man’s Sky - Alonso Guisande, Miguel Ángel; Lopez Fraile, Luis Antonio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
In today's digital society, user interactions in collaborative virtual spaces on the internet are transforming the audiovisual design of big-budget digital products, such as AAA video game productions. The virtual communities of fans of a popular digital product are highly relevant for their online presence, due to the significant influence of user-generated contributions. These fandom communities are collaborative virtual spaces where users share knowledge and experiences on a topic or audiovisual product of interest. This research focuses on the virtual community of fans of the procedural video game No Man's Sky in 2016 and how the contributions of the wiki fandom are reflected in the official updates published until February 2024. An exploratory study is proposed, which uses a scientific methodology based on the content analysis of registered users' interactions. The study consists of a virtual ethnography that identifies the audio content generated by the virtual community. The aim is to establish an effective correlation with the technological evolution of the video game analyzed, which has led to changes in the production of updates.